A poroviscohyperelastic model for numerical analysis of mechanical behavior of single chondrocyte. Issue 2 (25th January 2016) - Nguyen, Trung Dung; Oloyede, Adekunle; Gu, Yuantong
Abstract : The aim of this paper is to use a poroviscohyperelastic (PVHE) model, which is developed based on the porohyperelastic (PHE) model to explore the mechanical deformation properties of single chondrocytes. Both creep and relaxation responses are investigated by using finite element analysis models of micropipette aspiration and atomic force microscopy experiments, respectively. The newly developed PVHE model is compared thoroughly with the standard neo-Hookean solid and PHE models. It has been found that the PVHE can accurately capture both creep and stress relaxation behaviors of chondrocytes better than other two models. Hence, the PVHE is a promising model to investigate mechanical properties of single chondrocytes.